Research hotspots and trends of nanomaterials in stomatology: A bibliometric analysis from 2000 to 2023 - Liang, Lingyu; Han, Zongpu; Yang, Ruihan; Guo, Yuanlong; Chen, Zetao (Heliyon, 2024)
Nanomaterials (NMs) have emerged as highly promising candidates for stomatology due to their excellent quality and remarkable progress in recent years. However, with the rapid expansion of the research scale, challenges arise in the technological decision-making and research management processes, and therefore difficulty for researchers to understand the knowledge structure and research hotspots has increased significantly. This study aims to make a comprehensive summary of authors, institutions, journals, research topics, development trends, and research hotspots of NMs in stomatology through bibliometric analysis for the sake of providing references for scientific decision-making, research management, and academic exploration in this filed. Studies on research and application of NMs in stomatology were retrieved from the Web of Science Core Collection (WoSCC) from January 1, 2000 to April 27, 2023. Bibliometric analysis and visualization were conducted using CiteSpace and VOSviewer. A total of 620 articles were included in this study, showing a gradual increase in the number of publications focusing on NMs in stomatology. Globally, China ranked first with 130 publications, and the United States (US) enjoyed the highest citation count (n = 5218) and average citation per paper (ACP) (n = 52.18). The top three institutions with the highest publication output were the University of Sao Paulo (n = 22), the Chinese Academy of Sciences (n = 20), and Shanghai Jiaotong University (n = 13). The journals MATERIALS and NANOMATERIALS emerged as the most popular in this field (n = 20), and BIOMATERIALS had the highest co-citations (n = 1597). The most prolific author was Dos Reis and Andrea Candido (n = 7), while Thomas J. Webster enjoyed the highest co-citations (n = 94). Burstness analysis of the references revealed a prominent research focus on nanoparticle drug delivery systems (specifically lipid nanoparticles). Keyword burstness analysis identified "oxide nanoparticle" as the primary frontier keyword in this field. This is the first study of using bibliometric analysis to summarize the research trends and frontiers of NMs in stomatology. With progressive advancements in the research and application of NMs in oral healthcare, their academic impact is steadily increasing. China and the US maintain a leading position in this field. Future directions could primarily focus on the development and application of nanoparticle drug delivery systems (especially lipid nanoparticles) and metal oxide nanoparticles (especially in antibacterial aspects). We hope that this bibliometric analysis could provide researchers with a panoramic view and useful references for future research, thus promoting the development of NMs in stomatology. [Display omitted] . •This study represents the first comprehensive bibliometric analysis that summarizes the research trends and frontiers of nanomaterials in stomatology.•Reviews the literature and systematically examines countries/regions, institutions, authors, journals, references, and keywords related to nanomaterials in stomatology.•It may help researchers gain deeper insights into the development of nanomaterials in stomatology.